In Memoriam Professor Đorđe Fira (1959 - 2022) - Lozo, Jelena; Stanković, Slaviša (Archives of Biological Sciences, 2023)
Professor Đorđe Fira was someone who will be remembered by all who knew him with reverence and respect, whether as a professor, colleague, or friend. He graduated in 1981 from the Department of Molecular Biology and Physiology of the Department of Biological Sciences of the Faculty of Natural Sciences and Mathematics of the University of Belgrade and completed his postgraduate studies at the same faculty in 1985 with the defense of his master’s thesis. His interest in science developed at the Research and Development Department of the “PKB-Agroeconomics” Institute in the Laboratory of Microbiological Analysis in the period 1984-1989. As a scholarship holder from the U.S. Department of Agriculture, in 1987-1988 he studied at the Food Science Department, Cornell University, Ithaca, NY (USA). The Department of Biological Sciences at the Faculty of Natural Sciences became his home institution in 1989 when he was hired as an assistant professor in biochemistry. At that time, he was one of two assistants in the Chair of Biochemistry and Molecular Biology. He was involved in conducting practical exercises in various courses held by the professors of this Chair. In 1999, after defending his doctoral dissertation, he was elected Assistant Professor and started giving lectures in biochemistry for the then-newly established Ecology and Environmental Protection Study Group at the Faculty of Biology. He adapted the biochemistry course for this study group, bringing it in line with the development of a new direction in education, but also society, in which we are currently experiencing the importance of the issue of ecology and environmental protection today....